Different skills- differentiated learning plans - Soares, Filomena Baptista (2016)
Personal development and realisation through academic success is an overall objective of Higher Educational Institutions (HEI), promoting the embracement of an open and fruitful future to their students. These students enrol in several Higher Education courses after attending well distinguished secondary school programs. The impact of these different backgrounds, with its inherent differentiated basic skills, is a general and worldwide challenge, fundamentally when facing some specific “constructive” subjects like foreign languages and Mathematics. In this paper we present a project developed in a Math course, with the first year students from the Accounting and Management Bachelor Degree in the School of Management and Industrial Studies (ESEIG). This project, which started in the academic year 2012/13, proved to be a success, both in terms of acceptance by the students and course global assessment results. We will describe all the methodologic steps connected to its development, implementation and maintenance, ranging from project submission to Scientific and Pedagogical boards for approval, student’s background “characterisation”, teachers and staff involvement in the different parts of the project, among many others. The project results over the last three years will be presented, assessing its pros and cons and we will also analyse its transferability to other courses and/or subjects, one of our actual major concerns. Like any other project that tries to promote success in some “historically critical” courses, there are many obstacles, objections and problems both in its implementation and, moreover, in its pursuit. However, it is not possible to develop a conscientious work, when confronted with recurrent student’s difficulties, just “move forward” without even trying to change “something”.